Pengaruh Pendidikan Kewirausahaan dan Model Pembelajaran Teaching Factory terhadap Kesiapan Berwirausaha Siswa di SMK - Hasanah, Meilita Nur; Sojanah, Janah; Santoso, Budi (Jurnal Pendidikan Ekonomi Undiksha, 2023)
Education in entrepreneurship is a method of instilling and reinforcing entrepreneurial mindsets and routines. The teaching factory concept is a comprehensive approach to education. It is predicted that students would be better prepared for entrepreneurial endeavors if they are exposed to factory learning in the classroom. The teaching factory learning approach is supported by the application of entrepreneurship learning in shaping competence via industry-related school environmental units. This essay analyzes how the teaching factory learning model and entrepreneurship education affect students' ability to think creatively and take initiative. This study used a descriptive verification technique for its investigation